2008
DOI: 10.1126/science.1155085
|View full text |Cite|
|
Sign up to set email alerts
|

Plastin 3 Is a Protective Modifier of Autosomal Recessive Spinal Muscular Atrophy

Abstract: Homozygous deletion of the survival motor neuron 1 gene (SMN1) causes spinal muscular atrophy (SMA), the most frequent genetic cause of early childhood lethality. In rare instances, however, individuals are asymptomatic despite carrying the same SMN1 mutations as their affected siblings, thereby suggesting the influence of modifier genes. We discovered that unaffected SMN1-deleted females exhibit significantly higher expression of plastin 3 (PLS3) than their SMA-affected counterparts. We demonstrated that PLS3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

37
510
2
6

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 449 publications
(555 citation statements)
references
References 24 publications
37
510
2
6
Order By: Relevance
“…26,36 Another study reported families with unaffected SMN1-deleted females who had increased expression of the X chromosome gene plastin 3 (PLS3) compared with their SMA affected siblings. 9 Plastin 3 is important for axonogenesis and, therefore, was proposed as a protective modifier. It is possible that differential expression of PLS3 is modifying the SMA phenotype in the Hutterites, possibly accounting for the relatively early age of onset in the two affected boys and the milder phenotypes among females (including an asymptomatic woman), all of whom are homozygous for the same haplotype carrying 0 SMN1 and 2 SMN2 genes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…26,36 Another study reported families with unaffected SMN1-deleted females who had increased expression of the X chromosome gene plastin 3 (PLS3) compared with their SMA affected siblings. 9 Plastin 3 is important for axonogenesis and, therefore, was proposed as a protective modifier. It is possible that differential expression of PLS3 is modifying the SMA phenotype in the Hutterites, possibly accounting for the relatively early age of onset in the two affected boys and the milder phenotypes among females (including an asymptomatic woman), all of whom are homozygous for the same haplotype carrying 0 SMN1 and 2 SMN2 genes.…”
Section: Discussionmentioning
confidence: 99%
“…9,[25][26][27][28][29] The precise genetic modifiers that ameliorate the phenotype have not been determined in most cases, although a single base substitution in SMN2 (c.859G4C) enhances splicing of the gene, enabling it to partially or fully compensate for the lack of SMN1 in some cases. 25 However, the unaffected homozygous woman in our study did not carry this modifier.…”
Section: Identifying a Shared Haplotype In Affected Individualsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, since it has been shown that even diseased siblings with the same number of SMN2 genes can have different SMA phenotypes, many researchers thought that the SMN locus alone cannot explain the whole genetic basis for phenotypic variability of SMA [18,71]. To identify those putative SMA modifier genes, a transcriptome-wide differential expression analysis using total RNA from the lymphoblastoid cell lines derived from both unaffected and affected SMN1-deleted siblings was recently carried out by Wirth and collaborators [63]. In total, 18 transcripts showed a greater than threefold difference in expression, but only plastin 3 (PLS3, MIM# 300131) exhibited statistically significantly higher expression in fully asymptomatic siblings of all six SMA-discordant families analyzed [63].…”
Section: Smn Genes and Mutationsmentioning
confidence: 99%
“…To identify those putative SMA modifier genes, a transcriptome-wide differential expression analysis using total RNA from the lymphoblastoid cell lines derived from both unaffected and affected SMN1-deleted siblings was recently carried out by Wirth and collaborators [63]. In total, 18 transcripts showed a greater than threefold difference in expression, but only plastin 3 (PLS3, MIM# 300131) exhibited statistically significantly higher expression in fully asymptomatic siblings of all six SMA-discordant families analyzed [63]. All unaffected SMN1-deleted subjects were females and interestingly also the PST3 gene is localized on the sex-determining X chromosome.…”
Section: Smn Genes and Mutationsmentioning
confidence: 99%